Pengaruh Pembiayaan Murabahah, Musyarakah, Qardh Dan Mudharabah Terhadap Profitabilitas Bank Umum Syariah Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2019-2022 - Latifah Anum (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to examine the effect of murabahah, musyarakah, qardh and mudharbah financing on the profitability of Sharia Commercial Banks. The population in this research are companies in the Sharia Banking sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. The sampling technique used was purposive sampling. The number of Sharia Commercial Banks sampled in this research was 11 Sharia Commercial Banks. The test tool used in this research is SPSS 21. The findings in this research show that: (1) H0 is accepted and H1 is rejected, which means that Murabahah financing has no effect on the ROA (Y) profitability level of Sharia Commercial Banks for the 2019-2022 period. (2) H0 is accepted and H2 is rejected, which means that Musyarakah Financing has no effect on the ROA (Y) profitability level of Sharia Commercial Banks for the 2019- 2022 period. (3) H0 is accepted and H3 is rejected, which means Qardh financing has no effect on the ROA (Y) profitability level of Sharia Commercial Banks for the 2019-2022 period. (4) H0 is rejected and H4 is accepted, which means that Mudharabah Financing has an influence but a negative influence on the ROA (Y) profitability level of Sharia Commercial Banks for the 2019-2022 period.